EKSISTENSI DAN PERAN ROHANIWAN ASING TERHADAP PERKEMBANGAN KEHIDUPAN KEAGAMAAN DI KABUPATEN SIKKA, NTT - Ibnu Hasan Muchtar (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2016)
This paper aims to uncover the existence and role of Catholic foreign proselytizers servicing in Maumere. East Nusa Tenggara (NTT). It also describes the internal relationship between religious adherents as well as their subject to the existing regulations. The findings show that the number of foreign proselytizers outnumbers those who receive formal permit from the Ministry of Manpower, the Republic of Indonesia, because most of them have exceeded the regulation of internal relationship. Besides, every foreign proselytizer has their own vision and loyalty to the Bishop. In relation to the response of religious adherents other than Catholics, it has no significant effects because these foreign proselytizers did not interact with non-Catholic adherents.